The prospects of use of silicon photodiodes for registration alpha, beta radiation and neutrons - Voronkin, E.F.; Grinyov, B.V. (Functional Materials, 2016)
The purpose of the current work is an investigation of possibility of use of silicon photodiodes for registration alpha, beta radiations and neutrons. Electronic physical properties of the photodiodes which provide spectrometer characteristics of semiconductor detectors of nuclear radiations, such as: electronic noise, thickness of a sensitive layer, thickness of a surface not sensitive layer, are analyzed. It is shown that power permission for alpha particles is equal to 10-25 keV that which corresponds to resolution of the best surface-barrier semiconductor detectors. Also photodiodes can be used for measurement of a stream of beta particles, in spectrometry till energy value of 300 keV and for measurement of streams thermal and the fast neutrons with efficiency of about 1 %. Operational characteristics of the photodiodes allow use them in industrial platforms of nuclear objects and in the field conditions.